Interpersonal Online and Offline Communication as a Factor in Increasing Educational Motivation - Valeriya E. Mikhailova; Olga S. Parts (National Research Mordova State University, 2023)
Introduction. Online and offline formats of interpersonal communication are widespread and satisfy the need for communication and recognition of schoolchildren. At the same time, the issue of the peculiarities of using virtual interpersonal communication in learning activities, its potentials, formal and content parameters remains insufficiently studied. The purpose of the article is to analyze the possibilities of virtual format of interpersonal communication, which affects the needs, sources of activity, behavioral norms, and states of the child. Materials and Methods. In the course of an empirical study, the authors carried out a diagnosis of the success of online and offline communication in 238 students in Omsk schools. The parameters were studied in respondents using a set of diagnostic methods: the method "Diagnostics of motivational orientations in interpersonal communications (I. D. Ladanov, V. A. Urazaeva); the Rosenberg Self-Esteem Scale; methodology for diagnosing motivational-semantic formations (Yu. M. Orlov, B. A. Sosnovsky). Results. In the course of the study, it was revealed that the implementation of online and offline communication significantly increases all the parameters that characterize the success of interpersonal communication and educational motivation. Comparison of situations of face-to-face communication both online and offline allows us to say that in both cases interpersonal communication has a goal - the development of educational, social and cognitive motives. However, the process of online and offline communication not only supplements the personal plan with an emotional aspect, but also goes beyond the school educational space in terms of the "Result" and "Product" parameters. Discussion and Conclusion. The obtained results indicate that the functionality of communication in virtual space opens wider opportunities for the growth of educational motivation compared to face-to-face communication. The presented materials can be used by researchers of children's behavior in virtual space, teachers implementing blended or online learning.